ANALISIS STRATEGI DAN KEBIJAKAN BISNIS UMKM MIE BAEK EKSPRESS DI BOJONG SOANG - We Nabila Inang Torialena; Devin Nafiilah Alika; Maudy Shubiyanti; Aisyah Ainun Nabila; Karolina Stefani Sofia Loven; Muhammad Nadif (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This research aims to analyze problems related to business policy strategies in Micro, Small and Medium Enterprises (MSMEs), especially in the culinary sector, such as the Mie Baek Express business. In facing the Market competition and changes in business dynamics, effective business strategies and policies in terms of supply chains (suppliers) are determining factors for success. The problem focuses on various aspects in measuring how feasible the Mie Baek Express business is to be implemented. The method used in this research is descriptive analysis with a qualitative approach, data was collected through direct observation, interviews, and documentation studies as well as analysis carried out using internal SWOT analysis, 4P Marketing Mix, as well as external analysis of PESTEL and Porter's Five Forces. The research results show that Mie Baek Ekspress faces several serious challenges related to the quality and supply of constraints. One of the problems faced is that the noodle quality specifications are not good and often the noodle specifications do not match the initial agreement, which has a direct impact on the taste and texture of the final product. This problem often hampers the productivity of MSMEs, especially for businesses that are still developing and depend on suppliers as the main source of raw materials. With a structured strategy and policies that support migration, MSMEs in the culinary sector, especially in the Mie Baek Ekspress business, can improve their performance by diversifying suppliers to obtain more competitive raw materials and strengthening marketing strategies by utilizing social media which can help increase brand awareness. This can minimize the risk of a decline in MSME performance caused by poor supplier performance, so these MSMEs must have several alternative suppliers, and cooperation based on long contracts and making choices to create a sustainable business.